Molecular detection and genetic characterization of bovine hepacivirus identified in ticks collected from cattle in Harbin, northeastern China - Yuan, Sheng; Yao, Xin-Yan; Lian, Chun-Yang; Kong, Sa; Shao, Jian-Wei; Zhang, Xue-Lian (Frontiers in Veterinary Science, 2023)
Bovine hepacivirus (BovHepV) is a member of the genus Hepacivirus of the family Flaviviridae, which can cause acute or persistent infections in cattle. Currently, BovHepV strains identified in cattle populations worldwide can be classified into two genotypes with eight subtypes in genotype 1. BovHepV has been identified in a wide geographic area in China. Interestingly, the viral RNA of BovHepV has also been detected in ticks in Guangdong province, China. In this study, Rhipicephalus microplus tick samples were collected in Heilongjiang province, northeastern China, and BovHepV was screened with an overall positive rate of 10.9%. Sequence comparison and phylogenetic analysis showed that the BovHepV strains detected in this study belong to the subtype G. This is the first report about the detection of BovHepV in ticks in Heilongjiang province, China, which expands our knowledge that ticks may be a transmission vector of BovHepV.